The Influence of Financial Distress, Audit Firm Size, and Company Size on the Acceptance of Going Concern Opinions - Fachriyah, Nurul; Laily Anggraeni, Octadila (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
This study investigates the factors influencing the acceptance of going concern opinions (GCOs) among real estate companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2021. The primary aim is to explore the relationship between financial distress, audit firm size, and company size with the issuance of GCOs. Employing a qualitative research design, the analysis utilizes financial statement data to explore the relationships between financial distress, company size, and audit firm size on GCO issuance. The findings reveal that financial distress, as measured by the Altman Z-score, significantly increases the likelihood of receiving a GCO. Additionally, company size, represented by total assets, positively correlates with GCO acceptance, indicating that auditors are more likely to scrutinize larger firms. In contrast, the study finds no significant effect of audit firm size on GCO acceptance, suggesting that the financial conditions of the companies themselves are the primary determinants of auditor decisions regarding GCOs. These insights highlight the importance of financial health and transparency in maintaining stakeholder confidence in the real estate sector. The research contributes to the understanding of audit dynamics within Indonesia's real estate market and provides implications for corporate governance and regulatory frameworks. Future studies are encouraged to examine the qualitative aspects of the audit process and the decision-making criteria of auditors concerning GCO issuance.